Identifikasi Cendawan Patogen pada Beberapa Varietas Benih Padi Sawah Berdasarkan Model Penyimpanan - Kresentia Amteme; Anna Tefa (Fakultas Pertanian, Universitas Timor, 2018)
Seeds are said to be healthy if the seeds used are free of disease-causing microorganisms one of them is fungi. The purpose of this study was to obtain the type of pathogenic fungi that infect rice seeds. The research was conducted in the laboratory of Agricultural Faculty and Biology laboratory of Timor University since March - May 2017. The research used Completely Randomized Design of factorial pattern with two factors. The first factor consists of three varieties namely Ciherang, IR, and Siputih. The second factor consists of storage model ie storage in plastic sacks, Sokal, and cans. The results showed that the use of three varieties and models of seed packing material did not show any significant difference to germination. Maximum Growth Potential percentage between Siputih variety (97.33) was significantly different from IR varieties (72.00) and in seed model stored in the plastic sack (94.22) was significantly different from the seeds stored in the Sokal (68.88). Identification results found five fungi of the genus Aspergillus sp.1 and sp.2, Altenaria, Curvularia, Fusarium and Rhizopus that infect the seeds thus decreasing the germination power. The degree of fungal attack varies on varieties and storage models. The five fungal pathogens found, two fungi such as Aspergillus and Fusarium infect seeds with different storage areas lower, to reduce the infection rate of Altenaria fungus, Curvularia and Rhizopus can be treated fungicide.